EFFECT OF ANTICANCER DRUGS ON PRIMARY CELL CULTURES OF PATIENTS WITH COLORECTAL CANCER - N V Golyasnaya; Yu V Ivanov; N S Zhizhin (Клиническая практика, 2016)
The goal of the research is to estimate the effect of 5-Fluorouracil, Cisplatin, Tomudex, Leucovorin and their combinations on colorectal cancer cells in vitro. Cell response to the effect of cytotoxic compounds and immunomodulator was estimated by the change in chromosomal aberrations, cell growth rate, proliferative activity and colonyforming unit. It was detected that antineoplastic drugs affected the mutagenesis and fission rate of cultured cells.